人工智能熱須降溫: Need for Caution in Promoting AI - YE, Jinzhou (International Journal of Chinese & Comparative Philosophy of Medicine, 2019)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Robert Sparrow’s critical reflection on the growing enthusiasm for applying AI to medicine is timely and deeply thought provoking. Despite AI’s apparent benefits, its potential to restructure medical practice, the doctor–patient relationship and, more generally, human values in the long term give us every reason to be cautious. Before AI is fully embraced, its potential perils should be carefully considered. DOWNLOAD HISTORY | This article has been downloaded 25 times in Digital Commons before migrating into this platform.